Review of the Year 1931 - Crum, W. L.; Hubbard, J. B. (The Review of Economics and Statistics, 1932)
GENERAL business in the United States, already severely depressed at the close of I930, declined sharply during 193I; and, by the end of the year, the depression had become one of the longest and most destructive of which we have record. Early in the year some improvement actually appeared, and was reflected in numerous series measuring the volume of business. But this incipient revival was cut short as the world financial crisis became acute and introduced a new phase of contraction and liquidation. Even commodity prices showed some signs of stabilization during the year, especially in the third quarter; but the main course of prices continued downward, with the most severe declines affecting chiefly certain agricultural and mineral products entering largely into international trade. Severe as were the renewed curtailment in business activity and slump in commodity prices during I93I, with the attendant increased unemployment, reduced wage payments, impaired business earnings, and frequent commercial failures, the most sensational developments were in banking and currency. The overshadowing event of the year was the world monetary crisis, which reached its most acute stage in the drive on the gold standard of the United States in SeptemberOctober. For a few feverish weeks it was feared that the dollar as well as the pound would be driven from the gold basis. In spite of an unprecedented drain of gold abroad, suspension of gold payments in England, and stupendous shifts in the banking situation here, it presently became clear that the gold standard could be maintained in the United States. The panic then subsided, gold export halted and was followed by a substantial return flow, and the problems of reconstruction could be attacked with assurance that a greater disaster had been averted. The world crisis was accompanled, in its various phases, by the chief characteristic developments: huge international gold movements, from countries of impaired credit to the stronger centers; active flight from weakened currencies; widespread hoarding of currency, with preference for gold-standard currency rather than domestic currency; suspension of gold payments in numerous centers; acute banking difficulties, with severe liquidation of commodities and securities. In the United States, the banking system, already weakened by the prolonged depression and drastic liquidation, was subjected to an unprecedented strain. Hoarding, bank runs, and bank failures became more serious factors in the situation. The resulting pressure for liquidity in the closing months of the year contributed largely to the final wave of drastic liquidation which drove stock prices to new low levels and forced bond yields far above the current rates on money.